2008
DOI: 10.1002/eji.200737855
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte‐dependent oncostatin M and TNF‐α synergize to stimulate unopposed matrix metalloproteinase‐1/3 secretion from human lung fibroblasts in tuberculosis

Abstract: Leukocyte-derived matrix metalloproteinases (MMP) are implicated in the tissue destruction characteristic of tuberculosis (TB). The contribution of lung stromal cells to MMP activity in TB is unknown. Oncostatin M (OSM) is an important stimulus to extrapulmonary stromal MMP induction, but its role in regulation of pulmonary MMP secretion or pathophysiology of TB is unknown. We investigated OSM secretion from Mycobacterium tuberculosis (Mtb)-infected human monocytes/macrophages and the networking effects of suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
64
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 49 publications
6
64
0
Order By: Relevance
“…Since stromal cells are more numerous in the lung and may express relatively greater levels of MMPs than monocytic cells [61], they represent a potentially important source of MMPs in TB. Monocyteepithelilal cell networks upregulate MMP-1 and -9 [35,36], while monocyte-fibroblast networks upregulate MMP-1 and -3 [62,63]. In our cellular model of TB meningitis, monocyteastrocyte networks were found to upregulate MMP-1, -2, -3, -7 and -9 gene expression [41].…”
Section: Mmps Driven By Intercellular Networkmentioning
confidence: 68%
“…Since stromal cells are more numerous in the lung and may express relatively greater levels of MMPs than monocytic cells [61], they represent a potentially important source of MMPs in TB. Monocyteepithelilal cell networks upregulate MMP-1 and -9 [35,36], while monocyte-fibroblast networks upregulate MMP-1 and -3 [62,63]. In our cellular model of TB meningitis, monocyteastrocyte networks were found to upregulate MMP-1, -2, -3, -7 and -9 gene expression [41].…”
Section: Mmps Driven By Intercellular Networkmentioning
confidence: 68%
“…In work delineating the role of MMPs in pulmonary TB, we have demonstrated that MMP-9 is upregulated in M. tuberculosis infection by several cell types. However, upregulation of MMP-1 (collagenase-1) and MMP-3 (stromelysin-1, whose functions include MMP-1 activation) appeared relatively TB-specific (17)(18)(19). In CNS TB, we demonstrated that astrocytes secrete only MMP-9 (gelatinase B) in response to monocyte-dependent networks, despite upregulation of other MMP transcripts (20).…”
mentioning
confidence: 79%
“…The relative role of MMP-1 will be underestimated in this model, since stromal cell MMP secretion driven by M. tuberculosis will be absent (27,31,32). The lack of a functional ortholog of MMP-1 in mice would explain why infection of immunodeficient mice can result in extremely high bacterial loads and necrosis but cavitation does not occur (4,5).…”
Section: Discussionmentioning
confidence: 99%